Quality of life of infertile women as measured by WHOQOL-BREF in Bangladesh - Ishrat, Shakeela; Hossain, Marufa; Yasmin, Mahamuda; Akhter, Dilruba; Akter, Tasmin; Haque, Fatema; Shukla, Joyutpala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Quality of life (QoL) is lower in infertile women. Fertility expectations are as variable as social norms and culture and so is QoL. We expect to explore the QoL of infertile couple in a traditional society like that of Bangladesh. Methods: We measured the quality of the life of 88 infertile women attending the Department of Reproductive Endocrinology and Infertility, Bangabandhu Sheikh Mujib Medical University, with WHOQOL-BREF questionnaire, covering physical, psychological, social and environmental domains. The scores were calculated in the range of 4-20 and 0-100. Results: When we calculated in the range of 0-100, infertile women had mean score of 61.12 in physical, 54.78 in psychological, 70.36 in social and 58.63 in environmental domains. Nearly half (41.7%) of the women scored at or below 50 in psychological domain compared to 26% in physical, 14.6% in social and 28.1% in environmental domain. Conclusions: The QoL of infertile women as measured by WHOQOL-BREF has moderate scores. The women are disadvantaged in psychological domain compared to physical, social or environmental aspects. So, they need more psychological support during treatment.